Experimental Investigation of Minimum Quantity Lubrication on Tool Wear in Aluminum Alloy 6061-T6 using Different Cutting Tools - M., Puvanesan; M. M., Rahman; Najiha, M. S.; K., Kadirgama (Universiti Malaysia Pahang, 2014)
In manufacturing, a great challenge is currently being faced in the competitive marketing place due to the manufacturing environment, low costs, the aim to achieve high rates of productivity and also the demand for high quality from customers. Aluminum alloys are being competitively used in current industries, especially in the automotive and aeronautics sector. This study is for experimental investigation of minimum quantity lubricant (MQL) for the end milling machining characteristics regarding tool wear during the machining of aluminum alloy 6061-T6. Process parameters including the cutting speed, depth of cut and feed rate are selected for study to develop a model of process optimization based on the response surface method. This experiment was conducted based on the central composite design method. Three types of tools are used in this experiment, namely, high speed steel, coated and uncoated carbide tools. The encouraging results include a significant reduction in the tool wear rate with MQL mainly through the reduction in the cutting zone temperature and a favorable change in the chip–tool and work–tool interaction. It is concluded that the MQL technique leads to economic benefits in terms of reduced lubricant costs and better machinability.